Continuum Nonisomorphic Rational Groups - Ursul, Mihail (Topology Proceedings, 2020)
We construct a set of power of continuum nonisomorphic connected, rational, second metrizable Abelian topological groups. We also construct a nonmetrizable, connected, rational topological Abelian group.